2019
DOI: 10.1101/842492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of 3D markerless motion capture accuracy using OpenPose with multiple video cameras

Abstract: There is a need within human movement sciences for a markerless motion capture system, which is easy to use and sufficiently accurate to evaluate motor performance. This study aims to develop a 3D markerless motion capture technique, using OpenPose with multiple synchronized video cameras, and examine its accuracy in comparison with optical marker-based motion capture. Participants performed three motor tasks (walking, countermovement jumping, and ball throwing), with these movements measured using both marker… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Although markerless motionanalysis systems are less accurate than marker-based motion-analysis systems, the former system is more suitable for use in clinical rehabilitation and sports, where it is difficult to perform marker-based motion analysis. 23 A previous study reported that markerless motion analysis provided measurements with low validity, as tracking using an automated skeleton and relatively low camera sample rates was difficult. 24 In addition, a recent systematic review reported that the outcomes of low-cost video-based motion-analysis and 3D motion-analysis systems exhibited "poor" (r=0.025) to "strong" agreement (r=0.992).…”
Section: Discussionmentioning
confidence: 99%
“…Although markerless motionanalysis systems are less accurate than marker-based motion-analysis systems, the former system is more suitable for use in clinical rehabilitation and sports, where it is difficult to perform marker-based motion analysis. 23 A previous study reported that markerless motion analysis provided measurements with low validity, as tracking using an automated skeleton and relatively low camera sample rates was difficult. 24 In addition, a recent systematic review reported that the outcomes of low-cost video-based motion-analysis and 3D motion-analysis systems exhibited "poor" (r=0.025) to "strong" agreement (r=0.992).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements thus indicated that 3D pose estimation with marker-less motion capture was a correct reproduction of the test participants' movements. A rough estimate is therefore that the knee angle measurement has approximately the same accuracy as the proposal by Nakano et al 52 Schmitz et al 53 compare the accuracy of single camera markerless motion capture with a ten-camera marker-based motion analysis system for 6 different postures of a jig simulating a human leg. A digital inclinometer with an accuracy of 0.1° measured the abduction-adduction angles, which both the markerbased system and the marker-less system calculated as the mean of 30 frames.…”
Section: Use Triangulation a 2d Joint Coordinates Detected Bymentioning
confidence: 95%
“…Another proposal uses OpenPose with multiple synchronized video cameras to compare marker-less motion capture accuracy with optical marker-based motion capture accuracy for 2 tested participants' walking, countermovement jumping and ball throwing. 52 Mean absolute errors (MAE) measured test participants' corresponding joint position differences. For approximately 47% of all measurement MAE < 20 mm and for 80% of all measurement MAE < 30 mm.…”
Section: Use Triangulation a 2d Joint Coordinates Detected Bymentioning
confidence: 99%
“…Nakano examined the accuracy of the RGB based system in his research. He used Vicon as a reference system [4]. His research shows that the accuracy of detecting key points using standard cameras from a distance of several meters is about a few centimeters.…”
Section: Related Workmentioning
confidence: 99%